The Effectiveness of Slow Stroke Back Massage in Managing Chronic Pain Among Patients with Hypertension: Implications for Nursing Care - Wisuda, Aris Citra; Zalila, Rifka; Elyta, Tuti; Martha, Rian; Isrizal; Andika, Rindi (International Journal Scientific and Professional, 2025)
Hypertension is when a person experiences an increase in blood pressure above normal, or systolic pressure higher than 140 mmHg and diastolic pressure above 90 mmHg. Hypertension can cause headaches. One of the management techniques for headaches is non-pharmacological techniques, with slow stroke back massage (SSBM) therapy. This therapy is a massage action on the back with slow strokes. The purpose of this study was to determine the effectiveness of the slow stroke back massage technique in reducing the level of head pain in hypertensive patients. This research uses a descriptive method with a case study approach during the slow stroke back massage (SSBM) technique to reduce headaches in hypertensive patients. After nursing care for 3 days, the results of the headache scale on the first day were 6-7, on the second day, the headache scale also decreased, and on the third day, it decreased to 2. The slow stroke back massage (SSBM) technique can reduce headache levels in patients with hypertension